Emotional Regulation and Social Functioning in Patients with Schizophrenia - Romero-Ayuso, Dulce; García Arenas, José (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2020)
Introduction: Social disability is present in more than 50% of patients with schizophrenia after clinical remission. How emotional processing differs between patients with high and low social functioning has not been studied so far. Methods: A cross-sectional study was conducted, with 67 outpatients. The Social Functioning Scale and the Emotional Intelligence Test were used. Results: Statistically significant differences were found in Emotional Facilitation (p=0.007; d=0.74), in Emotional Management (p=0.003; d=0.83) and in all dimensions of social functioning, with a difference of up to 45.43 points between the groups. Conclusions: The results contribute to the understanding of the role played by emotional facilitation and regulation in social functioning.